Physicochemical and Catalytic Properties of Vanadia/Titania Catalysts. II. Textural Properties - Th. El-Nabarawy; M.N. Alaya; S.A. Sayed Ahmed; A.M. Youssef (Adsorption Science & Technology)
Titania gels, T a and T b , were precipitated from aqueous solutions of titanium tetrachloride at pH values of 3.0 and 9.0, respectively. Calcination products were obtained from these gels by thermal treatment at 300–1000°C. Vanadia/titania catalysts were obtained by impregnating T a and T b with ammonium vanadate to give products containing 4–12 wt% V 2 O 5 . These products were calcined at 400°C or 600°C, respectively. The adsorption of nitrogen at −196°C was followed and the isotherms thus obtained analyzed to enable the determination of the textural characteristics of the catalysts through the use of conventional methods of textural analysis. The specific surface area and total pore volume of titania decreased and its mean pore radius increased on increasing the calcination temperature from 400°C to 1000°C. Titania precipitated at pH 3.0 and calcined at 1000°C exhibited non-porous characteristics as indicated by the absence of hysteresis in the corresponding adsorption isotherm. The textural changes were attributed to the anatase → rutile transformation and also to the sintering of rutile. The specific surface area and porosity of vanadia/titania catalysts changed with increasing calcination temperature and with increasing vanadia content. However, the effect of calcination temperature was more pronounced.